2000
DOI: 10.1007/s001340000692
|View full text |Cite
|
Sign up to set email alerts
|

Use of a personal diary written on the ICU during critical illness

Abstract: A detailed narrative of the patient's stay is a useful tool in the debriefing process following intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
151
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 6 publications
3
151
2
7
Order By: Relevance
“…Of the 1439 titles screened, 1427 were excluded. Twelve full text articles were screened for potential inclusion, of which nine were excluded due to study design [1,22,[37][38][39][40][41][42][43]. This was because they did not use an RCT or CCT design.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 1439 titles screened, 1427 were excluded. Twelve full text articles were screened for potential inclusion, of which nine were excluded due to study design [1,22,[37][38][39][40][41][42][43]. This was because they did not use an RCT or CCT design.…”
Section: Search Resultsmentioning
confidence: 99%
“…This was because they did not use an RCT or CCT design. These included observational studies [22,38,[40][41][42][43], a prospective cohort study with retrospective reference group [39], time-series design [1] and a commentary paper [37]. Figure 1> Included studies Three studies were eligible to be included in the review.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient diaries show what occurred to the patient, and may be a way in which to fill memory gaps, to explain certain memories (Engström et al, 2008), and can offer the ICU staff a new insight as to how future care should be designed (Egerod and Christensen, 2009). Photographs are also taken (with the permission of the patient or next of kin), and put in to the diary Backman and Walther, 2001;Jones et al, 2010). Backman and Walther (2001) have shown that the use of photographs is appreciated by many patients.…”
Section: Introductionmentioning
confidence: 99%
“…Photographs are also taken (with the permission of the patient or next of kin), and put in to the diary Backman and Walther, 2001;Jones et al, 2010). Backman and Walther (2001) have shown that the use of photographs is appreciated by many patients. Patients who have been cared for in an ICU also expressed that a diary helped them gain an insight into the experience.…”
Section: Introductionmentioning
confidence: 99%